GRIN2A mutations in acquired epileptic aphasia and related childhood focal epilepsies and encephalopathies with speech and language dysfunction. - Lesca, G; Rudolf, G; Bruneau, N; Lozovaya, N; Labalme, A; Boutry-Kryza, N; Salmi, M; Tsintsadze, T; Addis, L; Motte, J; Wright, S; Tsintsadze, V; et al. (2013)
Epileptic encephalopathies are severe brain disorders with the epileptic component contributing to the worsening of cognitive and behavioral manifestations. Acquired epileptic aphasia (Landau-Kleffner syndrome, LKS) and continuous spike and waves during slow-wave sleep syndrome (CSWSS) represent rare and closely related childhood focal epileptic encephalopathies of unknown etiology. They show electroclinical overlap with rolandic epilepsy (the most frequent childhood focal epilepsy) and can be viewed as different clinical expressions of a single pathological entity situated at the crossroads of epileptic, speech, language, cognitive and behavioral disorders. Here we demonstrate that about 20% of cases of LKS, CSWSS and electroclinically atypical rolandic epilepsy often associated with speech impairment can have a genetic origin sustained by de novo or inherited mutations in the GRIN2A gene (encoding the N-methyl-D-aspartate (NMDA) glutamate receptor α2 subunit, GluN2A). The identification of GRIN2A as a major gene for these epileptic encephalopathies provides crucial insights into the underlying pathophysiology.